Continuous hydrothermal furfural production from xylose in a microreactor with dual-acid catalysts - Tongtummachat T. (2023)
An effective continuous furfural production from xylose in a microreactor over dual-acid catalysts was proposed. In this work, furfural was synthesized in an organic solvent-free system using formic acid and aluminum chloride as catalyst. The role of these catalysts in the consecutive reactions was examined and verified. The influence of operating conditions including xylose concentration, reaction temperature, residence time, total catalyst concentration, and catalyst ratio on the yield of furfural was investigated and optimized. The furfural yield of 92.2% was achieved at the reaction temperature of 180 °C, residence time of 15 min, catalyst molar ratio of 1 : 1, xylose concentration of 1 g L−1, and total catalyst concentration of 16 mM. The superior production performance of our process was highlighted in terms of the low catalyst concentration and short residence time compared to those of other systems based on the literature. In addition, a continuous in situ catalyst removal (purification) was demonstrated, providing further insights into the practical development of continuous furfural production.